MENGHADIRKAN “NABI”: Antara Hasrat dan Cinta dalam Ritus Shalawat Bersama pada Majelis Syubbanul Muslimin - Muzakki, Akhmad (Universitas Nurul Jadid, 2020)
This study seeks to position shalawat activities together as an arena for reproduction and consumption of religious capital through various socio-economic-cultural process. By making Syubbanul Muslimin an object of research, this study used sensory anthropological approach by means of analyzing the world and the actions of our informants and research subjects by walking, working, discussing the results of shooting, eating, and talking to informants. The results of this study showed that through practicing shalawatan, Prophet Muhammad was “presented” and “projected” in accordance with the local interpretation of the Muslim Majelis Syubbanul Muslimin. The event “Shalawat Bersama” is a rite of religion and / or art in Islam based on sufistic piety: shalawat, dhikr (prayer), and barokah (blessing) packed from the desire to love into a desire in the terms of mode of advanced capitalism.